Understanding the hydrologic impacts of wastewater treatment plant discharge to shallow groundwater: before and after plant shutdown. Issue 5 (30th June 2016) - Hubbard, Laura E.; Keefe, Steffanie H.; Kolpin, Dana W.; Barber, Larry B.; Duris, Joseph W.; Hutchinson, Kasey J.; Bradley, Paul M.
Abstract : WWTP cessation is a rare environmental event with far-ranging hydrologic effects. Results have implications for shallow-groundwater recharge and WWTP-derived contamination kilometers downstream from the outfall. Abstract : Effluent-impacted surface water has the potential to transport not only water, but wastewater-derived contaminants to shallow groundwater systems. To better understand the effects of effluent discharge on in-stream and near-stream hydrologic conditions in wastewater-impacted systems, water-level changes were monitored in hyporheic-zone and shallow-groundwater piezometers in a reach of Fourmile Creek adjacent to and downstream of the Ankeny (Iowa, USA) wastewater treatment plant (WWTP). Water-level changes were monitored from approximately 1.5 months before to 0.5 months after WWTP closure. Diurnal patterns in WWTP discharge were closely mirrored in stream and shallow-groundwater levels immediately upstream and up to 3 km downstream of the outfall, indicating that such discharge was the primary control on water levels before shutdown. The hydrologic response to WWTP shutdown was immediately observed throughout the study reach, verifying the far-reaching hydraulic connectivity and associated contaminant transport risk. The movement of WWTP effluent into alluvial aquifers has implications for potential WWTP-derived contamination of shallow groundwater far removed from the WWTP outfall.